The Effect of The Mechanic Competency Booster Program and Work Motivation on Mechanics’ Performance Through Competence as A Mediating Variable: A Study at Pt Pamapersada Nusantara, Aria District, Tanah Bumbu Regency - Ramadhani, Fajar Surya; Basuki, Basuki; Artiningsih, Dwi Wahyu (Syntax Literate, 2025)
The mining industry demands mechanical performance that is reliable, fast, and complies with safety standards. In this context, technical training and work motivation are crucial factors in shaping the quality of human resources. PT Pamapersada Nusantara, through the Mechanic Competency Booster (MCB) Program, aims to accelerate the competence development of contract-based mechanics (PKWT) through hands-on practice and staged coaching. In addition, work motivation is also believed to play a vital role in encouraging enthusiasm, responsibility, and initiative among mechanics in the field. Previous studies have highlighted the role of practical training and intrinsic motivation in improving technical performance, but few have tested their simultaneous effects by considering competence as a mediating variable. Therefore, this study attempts to fill that gap by examining the relationships among the MCB program, motivation, competence, and mechanic performance in a structured and quantitative manner. The study also reinforces its statistical findings with empirical field data through observations and interviews to ensure alignment between theoretical data and operational realities in the mining work environment. This study employs a quantitative approach using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Data were collected using a Likert-scale questionnaire distributed to 83 contract mechanics at the ARIA District, PT Pamapersada Nusantara. The research instrument consists of four latent variables: the MCB program, motivation, competence, and performance. The results show that both the MCB program and work motivation have a positive and significant effect on competence and mechanic performance. Motivation emerges as the most dominant factor in shaping competence, while the MCB program enhances technical readiness and independent work. Competence has a direct impact on improving task achievement and technical work efficiency. Furthermore, competence is also proven to significantly mediate the relationship between both the MCB program and motivation on performance, although the strength of this indirect effect is smaller than the direct path. These findings are supported by qualitative data from group leaders and instructors, who confirmed that field performance improves when mechanics are motivated and entrusted with independent responsibilities.